Increasing bioenergy production on arable land: Does the regional and local climate respond? Germany as a case study. Issue 6 (18th March 2014) - Tölle, Merja H.; Gutjahr, Oliver; Busch, Gerald; Thiele, Jan C.
<x xml:space="preserve">Abstract</x> The extent and magnitude of land cover change effect on local and regional future climate during the vegetation period due to different forms of bioenergy plants are quantified for extreme temperatures and energy fluxes. Furthermore, we vary the spatial extent of plant allocation on arable land and simulate alternative availability of transpiration water to mimic both rainfed agriculture and irrigation. We perform climate simulations down to 1 km scale for 1970‐1975 C20 and 2070‐2075 A1B over Germany with Consortium for Small‐Scale Modeling in Climate Mode. Here an impact analysis indicates a strong local influence due to land cover changes. The regional effect is decreased by two thirds of the magnitude of the local‐scale impact. The changes are largest locally for irrigated poplar with decreasing maximum temperatures by 1°C in summer months and increasing specific humidity by 0.15 g kg−1. The increased evapotranspiration may result in more precipitation. The increase of surface radiative fluxes Rnet due to changes in latent and sensible heat is estimated by 5 W m−2locally. Moreover, increases in the surface latent heat flux cause strong local evaporative cooling in the summer months, whereas the associated regional cooling effect is pronounced by increases in cloud cover. The changes on a regional scale are marginal and not significant. Increasing bioenergy production on arable land may result in local temperature changes but not in substantial regional climate change in Germany. We show the effect of agricultural practices during climate transitions in spring and fall.